Bit by Bit: Household Characteristics of Cryptocurrency Owners — Early Evidence From the 2019 Survey of Consumer Finances - Beavers, Randy; Godek, John (Journal of Applied Business and Economics, 2024)
Developments in financial technology over the past decade have increased the importance and use of cryptocurrency, though not much is known about the characteristics of cryptocurrency owners. Data on the ownership of cryptocurrency by U.S. households has recently been made available via the 2019 Survey of Consumer Finances. In the present research we identify key aspects that differentiate cryptocurrency owning households from those that do not. We find that households owning cryptocurrency tend to have a higher risk profile, especially pertaining to decisions concerning other investments, and demonstrate more financial acumen than households that do not own cryptocurrency. This has important implications as cryptocurrency ownership becomes more mainstream.